Impact of procedural time on clinical and angiographic outcomes in patients with acute ischemic stroke receiving endovascular treatment. (6th March 2019) - Hassan, Ameer E; Shariff, Umar; Saver, Jeffrey L; Goyal, Mayank; Liebeskind, David; Jahan, Reza; Qureshi, Adnan I
Abstract : Background: Procedural time in patients with acute ischemic stroke (AIS) undergoing mechanical thrombectomy may affect clinical outcomes. We performed a pooled analysis of the effect of procedural time on clinical outcomes using data from three prospective endovascular treatment trials. Objective: To examine the relationship between endovascular procedural time and clinical outcomes of patients with AIS following endovascular treatment. Methods: We analyzed data from SWIFT, STAR, and SWIFT PRIME studies, including baseline characteristics: National Institutes of Health Stroke Scale (NIHSS) score on admission, intracranial hemorrhage rates, and modified Rankin Scale score at 3 months. The Thrombolysis in Cerebral Infarction (TICI) scale was used to grade postprocedure recanalization. We recorded two procedural time intervals: (1) symptom onset to groin puncture and (2) groin puncture to angiographic recanalization. A multivariate analysis was performed using a logistic regression model to analyze predictors of unfavorable outcome. Results: We analyzed 301 patients who had undergone endovascular treatment and had near-complete or complete recanalization (TICI 2b or 3). At 3 months, 122 patients (40.5%) had unfavorable outcomes. The rate of favorable outcomes was significantly higher when the procedural time was <60 min compared with ≥60 min (62% vs 45%, p=0.020). Predictors of unfavorable outcome at 3 months were age (unit 10 years, OR=0.62, 95% CI 0.46 to 0.82, p<0.001), onset to groin puncture time (unit hour, OR=0.61, 95% CI 0.48 to 0.77, p<0.001), groin puncture to recanalization (unit 10 min, OR=0.89, 95% CI 0.80 to 0.99, p=0.032), baseline NIHSS score (20–28 vs 8–10, OR=0.17, 95% CI 0.05 to 0.62, p=0.018), and collaterals (OR=1.48, 95% CI 1.04 to 2.10, p=0.029). Conclusion: Procedural time in patients with stroke undergoing mechanical thrombectomy may be an important determinant of favorable outcomes in those with recanalization.